Evaluation method for surface treatment fillers
Patent Information
- Application Number
- JP2021160284
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-09-30
AI Technical Summary
【0013】 本発明の評価方法によれば、表面処理フィラーにおける被覆物の分布を簡便に評価することが出来る。その結果、例えば、表面処理熱伝導性フィラーにおける過剰な被覆物の層の有無について評価を行い、表面処理熱伝導性フィラーを使用した樹脂複合材料において、高い熱伝導率が得られない虞がある表面処理熱伝導性フィラーを、従来よりも簡便に選別することが可能となる。
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel method for evaluating surface-treated fillers, and more particularly to a method for evaluating surface-treated fillers by scanning the particle surface with a scanning probe microscope while vibrating the probe at a predetermined amplitude to obtain a phase image. [Background technology]
[0002] Resin composite materials obtained by compounding inorganic fillers with resins are used in a wide range of fields, such as heat dissipation materials. In order to improve the compatibility between the inorganic filler and the resin, it is common to use inorganic fillers that have been surface-treated (surface-treated fillers). By performing surface treatment, the filling property of the inorganic filler in the resin is improved, and it becomes easy to manufacture a resin composite material in which the inorganic filler is uniformly dispersed in the resin. The surface-treated filler is obtained by reacting an inorganic filler that has not been surface-treated (untreated filler) with a surface treatment agent, and forming a coating derived from the surface treatment agent on the surface of the particles.
[0003] Here, when the inorganic filler is a thermally conductive filler to be mixed into the heat dissipation material, performing a surface treatment to increase the filling property is an effective method for obtaining a resin composite material having a high thermal conductivity. However, if the surface treatment is not performed properly, for example, if the coating derived from the surface treatment agent is not uniformly distributed on the particle surface, the effect of the surface treatment may not be fully exerted. For example, if the distribution of the coating is uneven and there are parts that are not surface-treated, the compatibility with the resin is not sufficiently improved, making it difficult to obtain high filling property. In addition, if there is an excess layer of coating on the particle surface of the thermally conductive filler, the excess layer of coating may interrupt the heat path, and even if the filling property is increased, the thermal conductivity of the resin composition may not be improved as much as expected. Therefore, in the production of the surface-treated thermally conductive filler, it is important to confirm whether the surface treatment of the obtained surface-treated filler is performed appropriately, and in particular, to evaluate the distribution of the coating on the particle surface.
[0004] As a method for evaluating the surface treatment state of surface-treated particles, for example, the methods disclosed in Patent Documents 1 to 3 have been proposed.
[0005] Patent Document 1 discloses a method for evaluating the surface treatment state of a surface-treated filler by heating the filler to burn off the coating derived from the surface treatment agent, which is an organic substance, and measuring the thermal changes that occur during this process.
[0006] Patent Document 2 discloses a method for evaluating the surface treatment state by observing the change in pH when acid is dropped into a suspension of a surface-treated filler (magnesium hydroxide). This method is said to be able to accurately evaluate the coating state because the more uniform the surface treatment and the less exposed surface of the particles, the faster the rate of pH decrease.
[0007] In Patent Document 3, it is said that by immersing a surface-treated filler that has been surface-treated with a silane coupling agent (surface treatment agent) in alcohol, an alcohol having an alkoxy group in the silane coupling agent is generated, and this is quantified by gas chromatographic analysis, the reaction process and reaction rate between the filler and the silane coupling agent can be quantitatively and accurately evaluated.
[0008] However, in the conventional evaluation methods such as those described in Patent Documents 1 to 3, it is not possible to confirm the distribution of the coating, and it is difficult to perform a sufficient evaluation taking into account the distribution of the coating in the surface-treated filler. Therefore, in order to know with high accuracy, for example, the adverse effect that an excessive coating layer in the above-mentioned surface-treated thermally conductive filler has on thermal conductivity, the only way is to actually manufacture a resin composite material and measure the thermal conductivity, which is a time-consuming evaluation. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2001-85806 A [Patent Document 2] JP 2003-83950 A [Patent Document 3] JP 2004-108932 A Summary of the Invention [Problem to be solved by the invention]
[0010] As described above, it has been difficult to adequately evaluate the distribution of the coating by the conventional surface treatment state evaluation method. Therefore, the present invention aims to provide an evaluation method capable of evaluating the distribution of the coating in the surface-treated filler, in particular, the uniformity of the coating. [Means for solving the problem]
[0011] The present inventors conducted intensive research to solve the above problems, and as a result, discovered that it is possible to evaluate the distribution of coatings by scanning the particle surfaces of surface-treated particles while vibrating the probe of a scanning probe microscope at a predetermined amplitude to obtain a phase image.
[0012] That is, the present invention is a method for evaluating a surface-treated filler, which includes a step of scanning the particle surface of the surface-treated thermally conductive filler while vibrating the probe of a scanning probe microscope at a predetermined amplitude to obtain a phase image. Effect of the Invention
[0013] According to the evaluation method of the present invention, the distribution of the coating in the surface-treated filler can be easily evaluated. As a result, for example, the presence or absence of an excessive coating layer in the surface-treated thermally conductive filler can be evaluated, and it becomes possible to select a surface-treated thermally conductive filler that may not provide high thermal conductivity in a resin composite material using the surface-treated thermally conductive filler more easily than before. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In this specification, a filler that has been surface-treated with a surface treatment agent is referred to as a "surface-treated filler," and a filler before the surface treatment of the surface-treated filler or a filler produced under the same manufacturing conditions is referred to as an "untreated filler corresponding to the surface-treated filler" (sometimes simply referred to as an "untreated filler"). Furthermore, particles in a surface-treated filler are referred to as "surface-treated particles," and particles in an untreated filler are referred to as "untreated particles." The organic matter originating from the surface treatment agent present on the surface of the surface-treated particles is referred to as a "coating," and the raw material for forming the coating is referred to as a "surface treatment agent corresponding to the surface-treated filler" (sometimes simply referred to as a "surface treatment agent").
[0015] The surface-treated filler evaluated by the evaluation method of the present invention is not particularly limited, and for example, the evaluation method of the present invention can be applied to surface-treated silica, alumina, aluminum nitride, boron nitride, etc. The particle size of the surface-treated filler is not particularly limited, but since a small particle size makes evaluation difficult and a large particle size requires a long time for evaluation, the particle size is preferably 0.5 μm to 100 μm, and more preferably 1.0 μm to 10 μm.
[0016] The surface treatment agent is not particularly limited, and any known agent can be used, such as a silane coupling agent.
[0017] A scanning probe microscope is a device that evaluates the surface condition of a measurement object by scanning the surface of the measurement object while moving the probe to trace the surface and detecting the interaction between the probe and the measurement object. In the evaluation method of the present invention, the particle surface of the surface-treated particle is scanned while vibrating the probe at a predetermined amplitude to perform measurement and obtain a phase image. When comparing the phase when the sample surface is scanned with the phase when the probe is vibrated at a predetermined amplitude, when a soft part is scanned, the phase delay due to the adsorption of the probe to the particle surface is large, and when a hard part is scanned, the phase delay is small, so the degree of hardness of the part can be evaluated from the obtained phase image. And, since the part where a lot of coating is present in the surface-treated particle is soft, it is presumed that the distribution of coating on the particle surface can be evaluated from the phase image obtained by this measurement.
[0018] The scanning probe microscope used in the evaluation method of the present invention is not particularly limited as long as it is capable of carrying out the above measurements.
[0019] The type of probe used in the evaluation method of the present invention is not particularly limited, but in order to obtain high resolution, it is preferable that the radius of curvature of the probe tip is 5 to 100 nm.
[0020] In the evaluation method of the present invention, the method of placing the measurement sample on the scanning probe microscope is not particularly limited as long as the above measurement can be performed, but for example, after dispersing particles in a volatile solvent to prepare a dispersion liquid, the dispersion liquid is dropped onto a mica substrate, and the measurement substrate prepared by volatilizing the volatile solvent is fixed to the sample stage of the scanning probe microscope with conductive carbon tape. The volatile solvent is not particularly limited as long as it can disperse the particles to be measured and does not react with the particles, and for example, alcohols such as methanol, ethanol, propanol, isopropyl alcohol, and butanol, ketones such as acetone, methyl ethyl ketone, diethyl ketone, and methyl isobutyl ketone, ethers such as diethyl ether, dioxane, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, and tetrahydrofuran, alkanes such as hexane, 2-methylpentane, heptane, cyclohexane, octane, 2,2,4-trimethylpentane, and petroleum ether, esters such as ethyl formate, butyl formate, ethyl acetate, propyl acetate, and butyl acetate, benzene, toluene, xylene, and naphthalene can be used.
[0021] In the evaluation method of the present invention, a cantilever holder with a cantilever having a probe at its tip is attached to a scanning probe microscope, and then the cantilever is excited at a resonant frequency to scan the sample surface, and the height displacement and phase shift of the cantilever are detected and imaged, making it possible to confirm the change in phase of the sample surface. The amplitude and gain of the probe can be adjusted so that a roughness image of the particles can be obtained.
[0022] In the evaluation method of the present invention, the probe is scanned over the entire surface of the surface-treated particle in the surface-treated filler, thereby making it possible to confirm the distribution of hardness of the surface of the surface-treated particle, and it is possible to evaluate the uniformity of the coating from this hardness distribution. There is no particular limitation on the method for evaluating the hardness distribution of the surface-treated particle from the obtained data, but it can be performed, for example, by confirming a phase image showing the phase delay as a contrast.
[0023] By measuring a plurality of particles in the surface-treated filler, the properties of the surface-treated filler can be understood. The number of surface-treated particles to be measured to understand the properties of the surface-treated filler is not particularly limited, but since the evaluation accuracy can be improved by measuring a larger number of particles, the number of particles is preferably 5 or more per 500 g of filler, and more preferably 10 or more.
[0024] By carrying out the evaluation method of the present invention, a topographical image of the particle surface can also be obtained at the same time. Since the area where the coating material is excessively present is often higher than the surrounding area, evaluation based on the topographical image may also be carried out.
[0025] The evaluation method of the present invention makes it possible to evaluate the uniformity of the coating on the particle surface of a surface-treated filler, which makes it easier to control the quality of the surface-treated filler and to examine the manufacturing conditions.
[0026] By evaluating the uniformity of the coating by this evaluation method, for example, fillers that may not be highly packed because part of the particle surface is not surface-treated and may not blend well with the resin, or fillers that may have an excessive layer of coating that may cause a decrease in thermal conductivity, can be selected. This makes it possible to efficiently control the quality of surface-treated fillers. Specifically, for example, when both high packing and high thermal conductivity are required for a thermally conductive filler to be filled into a resin, this evaluation method is performed, and if the distribution of the coating is uneven, it is highly likely that at least one of the high packing and high thermal conductivity is insufficient, and it can be determined that the requirement is not met.
[0027] For example, in the case where a high thermal conductivity is required for a thermally conductive filler, but the expected amount of filling into the resin is small and high filling is not necessary, a filler in which a part of the particle surface is not surface-treated, which makes it difficult to blend with the resin and does not provide high filling will meet the requirement, while a filler with an excessive layer of coating that causes a decrease in thermal conductivity will not meet the requirement. In such a case, it is difficult to distinguish between these two states using only the evaluation method of the present invention, but the accuracy of the judgment can be increased by combining an evaluation that can confirm that a sufficient amount of coating is present on the surface-treated filler (for example, the carbon amount or M value of the surface-treated filler) with the evaluation method of the present invention. Specifically, for fillers that are determined to have an uneven coating in the evaluation of the present invention, the surface treatment state is evaluated based on the carbon content and M value, and it is possible to determine that if the surface is sufficiently treated, the filler does not meet the requirement of high thermal conductivity because an excessive coating layer is present, although high filling can be obtained. Conversely, if the surface is not sufficiently treated, part of the particle surface is not surface treated, resulting in an uneven distribution of the coating, but there is no excessive coating layer, and the filler meets the requirement of high thermal conductivity.
[0028] In addition, after confirming through evaluation of the carbon content, M value, etc. of the surface-treated filler that sufficient coating is present on the particle surface and high filling properties can be obtained, the evaluation method of the present invention can also be used for the purpose of selecting fillers that may have an excessive coating layer that may cause a decrease in thermal conductivity. EXAMPLES
[0029] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The samples used for evaluation are as follows.
[0030] Aluminum Nitride Powder A1: Aluminum nitride powder (non-surface-treated aluminum nitride powder, average particle size 1 μm, manufactured by Tokuyama Corporation) · B1, 2: A1 treated with alkyl silane coupling agent S1 according to the surface treatment method below. The carbon amounts of B1 and B2 measured by a carbon analyzer are equivalent. · C1, 2: A1 treated with epoxy-based silane coupling agent S2 according to the surface treatment method below. The carbon amounts measured by a carbon analyzer for C1 and C2 are equivalent. D1, 2: A1 treated with methacrylic silane coupling agent S3 according to the surface treatment method below. The carbon amounts measured by a carbon analyzer for D1 and D2 are equivalent. E1, 2: A1 treated with phenyl-based silane coupling agent S4 according to the surface treatment method below. The carbon amounts of E1 and E2 measured by a carbon analyzer are equivalent.
[0031] <Surface treatment method for aluminum nitride powder> 500g of aluminum nitride powder A1, a specified amount of silane coupling agent, and 600g of isopropyl alcohol were placed in a glass eggplant flask and stirred with a fluororesin stirring blade for 30 minutes. After removing the isopropyl alcohol under reduced pressure using a rotary evaporator, the mixture was dried under reduced pressure at 100°C to obtain a surface-treated aluminum nitride powder. The obtained surface-treated aluminum nitride powder weighed about 500g.
[0032] <Filler evaluation method> 0.005 g of filler and 10 g of ethanol were placed in a 50 mL screw tube bottle and irradiated with ultrasonic waves for 15 minutes in an ultrasonic bath to prepare a sample dispersion. The prepared sample dispersion was collected with a dropper and dropped onto a 10 mm square mica substrate, and then dried at 80°C to remove the ethanol to obtain a measurement substrate. The measurement substrate obtained was fixed to the sample stage of a scanning probe microscope (Bruker: Dimension Icon) using double-sided tape. Next, particles with a particle size of 1 μm to 10 μm were selected, and the cantilever was scanned with a probe while vibrating at a resonance frequency to obtain a height image and a phase image. The amplitude and gain of the probe were adjusted so that a roughness image of the particles was obtained. After phase images were obtained for 10 particles, evaluation was performed using the obtained phase images.
[0033] <Evaluation of thermal conductivity> A resin composite material was prepared by kneading 1g of two-liquid addition reaction type silicone resin and 5g of filler in an agate mortar. The thermal conductivity of the prepared resin composite material was measured by the laser flash method to evaluate the thermal conductivity of the resin composite material.
[0034] <Example 1> When fillers B1 and B2 were evaluated according to the above-mentioned filler evaluation method, filler B1 had fewer locations where phase lag was observed than filler B2. Furthermore, when the thermal conductivity of resin composite materials containing these fillers was evaluated according to the above-mentioned thermal conductivity evaluation, the resin composite material using filler B1 had a higher thermal conductivity than the resin composite material using filler B2. Fillers B1 and B2 had the same amount of carbon measured by a carbon analyzer, so it was believed that the amount of coating was the same and that both had sufficient surface treatment. However, according to the evaluation method of the present invention, differences were observed in the phase images, and it was believed that filler B2 had a lower uniformity of coating. When a resin composition was actually produced and its thermal conductivity was evaluated, the resin composition using filler B2, which showed a phase delay, showed a lower thermal conductivity. Therefore, it can be said that the evaluation method of the present invention makes it possible to select fillers that may have an excessive coating layer that may cause a decrease in thermal conductivity from fillers that have a sufficient coating on the particle surface.
[0035] <Example 2> When fillers C1 and C2 were evaluated according to the above-mentioned filler evaluation method, filler C1 had fewer locations where phase lag was observed than filler C2. Furthermore, when the thermal conductivity of resin composite materials containing these fillers was evaluated according to the above-mentioned thermal conductivity evaluation, the resin composite material using filler C1 had a higher thermal conductivity than the resin composite material using filler C2. Therefore, as in Example 1, it can be said that the evaluation method of the present invention made it possible to select fillers that may have an excessive coating layer that may cause a decrease in thermal conductivity from fillers that have a sufficient coating on the particle surface.
[0036] <Example 3> Fillers D1 and D2 were evaluated according to the above-mentioned filler evaluation method, and filler D1 had fewer locations where phase lag was observed than filler D2. Furthermore, when the thermal conductivity of resin composite materials containing these fillers was evaluated according to the above-mentioned thermal conductivity evaluation, the resin composite material using filler D1 had a higher thermal conductivity than the resin composite material using filler D2. Therefore, as in Example 1, it can be said that the evaluation method of the present invention made it possible to select fillers that may have an excessive coating layer that may cause a decrease in thermal conductivity from fillers that have a sufficient coating on the particle surface.
[0037] <Example 4> When fillers E1 and E2 were evaluated according to the above-mentioned filler evaluation method, filler E1 had fewer locations where phase lag was observed than filler E2. Furthermore, when the thermal conductivity of resin composite materials containing these fillers was evaluated according to the above-mentioned thermal conductivity evaluation, the resin composite material using filler E1 had a higher thermal conductivity than the resin composite material using filler E2. Therefore, as in Example 1, it can be said that the evaluation method of the present invention made it possible to select fillers that may have an excessive coating layer that may cause a decrease in thermal conductivity from fillers that have a sufficient coating on the particle surface.
Claims
[Claim 1] A method for evaluating a surface-treated filler, comprising the steps of: scanning the particle surface of the surface-treated filler while vibrating a probe with a predetermined amplitude using a scanning probe microscope; obtaining a phase image showing a phase delay in contrast; and using the phase image to confirm the distribution of surface hardness of the surface-treated particles in the surface-treated filler, and to evaluate the uniformity of the coating.
Citation Information
Patent Citations
Method for inspecting surface-treated state of filler for resin of wiring board, treatment method, and the wiring board.
JP2001085806A
Method for evaluating surface covering state in magnesium hydroxide based flame retarder
JP2003083950A
Method for evaluating reaction rate of silane coupling agent used for surface treatment of inorganic filler
JP2004108932A
Electroconductive particles, and electroconductive material and connection structure using same
WO2021235434A1